On the mechanisms of formation and decomposition of peptide bonds. Issue 21 (January 2020) - Bolognesi, P; Chiarinelli, J; Richter, R; Stockett, M H; Indrajith, S; Nicolafrancesco, C; Eklund, G; Zettergren, H; Sa'adeh, H; Domaracka, A; Rousseau, P; Avaldi, L
Synopsis: The electronic structure and the fragmentation dynamics of a series of isolated cyclic-dipeptides (cyclo-Ala-Ala; cyclo-Gly-Ala; cyclo-Gly-Gly) have been studied by mass spectrometry, photoemission and photoelectron-photoion coincidence spectroscopy.